2020
DOI: 10.1088/1757-899x/805/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles from leaf extract of Tetrapleura tetraptera and its antimicrobial activity

Abstract: Plants have very high potential as alternative source of bio-reducing and capping agents in nanoparticles (NPs) synthesis. Silver nanoparticles (AgNPs) were synthesized from Tetrapleura tetraptera leaf extract. The UV-vis spectrophotometer was used to observe the formation of the NPs at various time intervals and ratios of leaf extract to AgNO3 solution. The properties of the AgNPs synthesized were characterized by FTIR and Scanning Electron Microscope (SEM) equipped with Energy Dispersive X-ray Spectroscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In earlier works, the SPR band of silver nanoparticles synthesised by sunlight irradiation was observed at 428.7 nm [47]. The silver nanoparticles synthesised by heating of silver nitrate solution and S. nodiflora leaf extract showed SPR peak at 460 nm [48].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier works, the SPR band of silver nanoparticles synthesised by sunlight irradiation was observed at 428.7 nm [47]. The silver nanoparticles synthesised by heating of silver nitrate solution and S. nodiflora leaf extract showed SPR peak at 460 nm [48].…”
Section: Resultsmentioning
confidence: 99%
“…The nanoparticles could also inhibit DNA replication by reacting with the phosphorus or sulphur moieties of DNA [59]. It was reported that the silver nanoparticles synthesised by using S. nodiflora leaf extract with the aid of sunlight irradiation and heating methods also showed antimicrobial activities [47,48]. Also, the bactericidal activities of nanoparticles were higher for gram negative bacteria compared to gram positive bacteria.…”
Section: Antimicrobial Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The GC also displayed a sharp peak and multiple band absorption around 996 cm −1 in the fingerprint region which shows the vibration of the glucose C─O─C in the GC (Ogunsile et al, 2020). The result of this study relates to the report of Kayode et al (2021) on frozen cassava root which may be due to the fact that cassava roots is used for the production of gari as used in their study.…”
Section: Resultsmentioning
confidence: 99%
“…The plant extracts containing different concentrations and combinations of organic compounds such as alkaloids and flavonoids act both as reducing and stabilizing agents to reduce metallic salt to metallic nanoparticles 6&7 . Metal nanoparticles (MNPs) are NP obtained from the reduction of metal salts, they have a wide range of biomedical applications which include; their use as imaging-resource, multifunctional theranostic abilities, efficient antibacterial, antifungal, and antiviral agents, antitumor, and drug carrier properties [7][8][9][10] . Metal NPs exhibit unique physicochemical properties which are a result of their size and shape relationship 11&12 .…”
Section: Introductionmentioning
confidence: 99%